Clergy's Viewpoint Change Toward Mental Health and Stigma on Mental Illness: A Short Course Training - Taghva, Arsia; Noorbala, Ahmad Ali; Khademi, Mojgan; Shahriari, Alireza; Nasr Esfahani, Mahdi; Asadi, Ali; Mohsenifar, Jafar; Yousefifard, Ali; Abolhassani, Moussa; Bolhari, Jafar; Hajebi, Ahmad; Rahnejat, Amir Mohsen; et al. (Frontiers in Psychiatry, 2022)
Background As stigma is one of the main barriers in promoting the mental health, the present study was designed with the purpose of reviewing clergy's viewpoint regarding the effect of mental health workshops on these barriers. Methods For this study, by order of Iran's Health Ministry, a questionnaire was designed to examine the clergy's viewpoint related to mental illnesses and the consequent stigma. Ten faculty members and psychiatrists confirmed the questionnaire's validity after some modifications. In this research, 30 members of the clergy from the main religious city in Iran's “Qom” Seminary attended the training workshops for 2 days. The data obtained from the clergy's responses were analyzed using the SPSS software (ver.16) and descriptive and analytical tests. Also, the significance level was considered p < 0.05 in all tests. The results exhibited that the mean and standard deviation (Mean ± SD) of the clergy's attitude domain and awareness before the workshop was 1.90 ± 26.30 and 8.31 ± 1.64, respectively. Also, average and standard deviation (Mean ± SD) of their attitude domain and awareness after the workshop was 1.95 ± 29.73 and 1.18 ± 10.70, respectively. Discussion The present study, which was designed to examine the clergy's viewpoint toward mental illnesses and the consequent stigma in the most considerable religious base in the country, illustrated that one strategy for reducing mental illness stigma in religious communities can be by holding training sessions to promote the clergy's awareness of and attitude toward mental health. Conclusion There was a significant statistical difference between their awareness and attitude scores before and after the workshop (p < 0.01). In the present research, the awareness and attitude of clergy toward mental health and stigma due to mental illness was relatively good and significantly increased by holding the workshop.